2023
DOI: 10.1021/acsami.3c02559
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Osmosis in Charged Nanochannels: Effects of Surface Charge and Ionic Strength

Abstract: Thermo-osmosis refers to fluid migration due to the temperature gradient. The mechanistic understanding of thermo-osmosis in charged nano-porous media is still incomplete, while it is important for several environmental and energy applications, such as low-grade waste heat recovery, wastewater recovery, fuel cells, and nuclear waste storage. This paper presents results from a series of molecular dynamics simulations of thermo-osmosis in charged silica nanochannels that advance the understanding of the phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…41 Secondly, for an electrically neutral surface, there is a change of sign of the enthalpy excess, indicating a change of direction of the thermo-osmotic flow, again being consistent with a previous study that reports a change of direction of the flow when changing the wetting of the system. 26 On silica-based materials, which have hydrophilic surfaces, it has been shown that the surface charge density can affect the thermo-osmotic flow direction, this effect being attributed to a change of sign of the enthalpy excess, 23,36 our calculations tend to confirm qualitatively the results of these studies.…”
Section: Effect Of Wetting Propertiessupporting
confidence: 77%
See 2 more Smart Citations
“…41 Secondly, for an electrically neutral surface, there is a change of sign of the enthalpy excess, indicating a change of direction of the thermo-osmotic flow, again being consistent with a previous study that reports a change of direction of the flow when changing the wetting of the system. 26 On silica-based materials, which have hydrophilic surfaces, it has been shown that the surface charge density can affect the thermo-osmotic flow direction, this effect being attributed to a change of sign of the enthalpy excess, 23,36 our calculations tend to confirm qualitatively the results of these studies.…”
Section: Effect Of Wetting Propertiessupporting
confidence: 77%
“…There is an increasing effort to better understand thermo-osmotic flows, through experimental characterization 23,24 and modeling. [25][26][27][28][29][30][31][32][33][34][35][36][37] As detailed in the Theory section, for liquids, Derjaguin and collaborators developed a standard theoretical framework, 13,[38][39][40] which relates the thermo-osmotic flow velocity to the interfacial enthalpy excess, stemming from the interactions of the liquid with the solid. This framework has been extended recently to take into account liquid-solid slippage arising on low-friction surfaces, 13,26,41 which can boost the flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation